2002
DOI: 10.3989/gya.2002.v53.i2.309
|View full text |Cite
|
Sign up to set email alerts
|

Studies on drying kinetics of olive foot cake

Abstract: Estudios sobre la cinética de secado del orujo. El orujo es un importante subproducto de la industria del aceite de oliva ya que puede contener hasta el 12% del aceite, el cual puede ser extraído usando un disolvente apropiado. El uso del disolvente es a menudo inmiscible con el agua. Esta es la razón por la que su efecto está limitado por la humedad del orujo, haciendo su secado imperativo. En este artículo se presenta el comportamiento del orujo so metid o a un seca do po r c onvección. Los resultados experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 1 publication
2
1
0
Order By: Relevance
“…It can be seen that moisture ratio decreases continuously with drying time, and no constant drying rate period exists. This observation is in agreement with previous literature studies on drying of olive cake (Gogus & Maskan, 2001;Kadi & Hamlat, 2002). The rate of moisture loss was high initially.…”
Section: Analysis Of the Drying Curvessupporting
confidence: 94%
“…It can be seen that moisture ratio decreases continuously with drying time, and no constant drying rate period exists. This observation is in agreement with previous literature studies on drying of olive cake (Gogus & Maskan, 2001;Kadi & Hamlat, 2002). The rate of moisture loss was high initially.…”
Section: Analysis Of the Drying Curvessupporting
confidence: 94%
“…The MR of the samples reduced exponentially with drying time. The results agreed with the previous studies about varied materials when dried (Gogus and Maskan, 2001;Kadi and Hamlat, 2002). (Fijalkowska et al, 2016).…”
Section: Results and Discussion Effects Of Pretreatments On The Drying Characteristicssupporting
confidence: 93%
“…Drying was stopped when moisture content was 12%. This moisture content value for prina sample that has 7 mm layer thickness was obtained after 13250 seconds for 90 W, 1070 seconds for 360 W and 820 seconds for 600 W. It was obtained for 9 mm layer thickness after 17640 seconds for [23,24] . It can be concluded that drying time decreased by increasing of temperature whereas the drying time increased by increasing of prina layer thickness.…”
Section: Results On Microwave Dryingmentioning
confidence: 99%